Pengembangan Model Pembelajaran Berbasis Kearifan Lokal pada Mata Pelajaran Bahasa Indonesia SMA - Ralis Zalukhu; Margareta Meiwati Laia; Wita Kurniawati Waruwu; Noveri Amal Jaya Harefa (Departement of Mathematics Education, 2023)
Although learning Indonesian is a required topic at school, many students despise the subject since the learning process is so tedious. A way to raising students' interest in learning about Indonesian language subjects is the availability of a learning model based on local wisdom. The feasibility test results for the research and development (R&D) development model obtained an 87% percentage and a 97% practicality test result, indicating that it was practicable to apply this learning model.